Water-chemistry operating condition of the second circuit power units №1-4 Rivne NPP with ethanolamine`s corrective treatment - Kuznetsov, P.N.; Tichomirov, A.U. (Вопросы атомной науки и техники, 2017)
The analysis of ethanolamine (ETA) operation results water-chemistry condition (WCC) of the second circuit power units No 1-4 Rivne NPP was provided. The control data in the experimental and industrial exploitation ETA WCC (2006-2016 years), assessment and evaluation of the steam generators operating condensate systems (FSD BOU) and clean steam generator blow down water (SVO-5) at maintaining the water-chemistry of ETA was systematizated and summarising. Проведено аналіз результатів експлуатації етаноламінового (ЕТА) водно-хімічного режиму (ВХР) другого контура на енергоблоках №1-4 Рівненської АЕС, систематизовані та узагальнені дані контролю при дослідній та промисловій експлуатації ЕТА ВХР (2006-2016 рр.), дано оцінки стану парогенераторів, експлуатації систем конденсатоочищення (ФЗД БЗУ) і очищення продувочної води парогенераторів (СВО-5) при підтриманні ЕТА ВХР. Проведен анализ результатов эксплуатации этаноламинового (ЭТА) водно-химического режима (ВХР) второго контура на энергоблоках №1-4 Ровенской АЭС, систематизированы и обобщены данные контроля при опытной и промышленной эксплуатации ЭТА ВХР (2006-2016 гг.), даны оценки состояния парогенераторов, эксплуатации систем конденсатоочистки (ФСД БОУ) и очистки продувочной воды парогенераторов (СВО-5) при поддержании ЭТА ВХР.